Business Development Strategy Model of SMEs Through SWOT and EFE-IFE Analysis - Iha Haryani Hatta; Dian Riskarini; Tia Ichwani (Universitas Islam Negeri Raden Mas Said Surakarta, 2018)
Considering that the SME entrepreneurs of Gresik Regency are mostly young, educated and experienced, however their businesses are not yet in legal entities. This research situates the SME business development strategy model through SWOT and EFE-EFI analysis, aiming to identify the conditions and models of SME business development strategies to improve their performances. This research has interviewed 40 respondents who were selected in multi stage, and analyzed through SWOT and EFE-IFE analysis. The result of this research explains that the ability of SME entrepreneurs in managing business and the achievement level of marketing performance is good, except the ability to manage finances. In addition, external conditions support these SMEs.Â Keywords: SWOT, EFE-IFE, business development strategy, SMEs